SEISMIC PROTECTION OF LOW-RISE LARGE-PANEL AND MODULAR FRAME BUILDINGS FROM POWERFUL EARTHQUAKES - Marienkov М.; Babik К.; Lysytsia М.; Khymenko Б. (Bulletin of Lviv National Environmental University. Series «Architecture and Construction», 2024)
During the period of 2022–2024, many residential buildings were destroyed during shelling and bombing in Ukraine. Therefore, providing housing for the affected residents is an urgent problem. Solving this problem in a short period is possible due to the construction of prefabricated low-rise and modular houses. Ensuring the seismic resistance of buildings during construction in highly seismic zones (with the intensity of earthquakes of 8 and 9 points according to the seismic intensity scale) requires the installation of seismic protection. The use of prefabricated large-panel low-rise and frame modular buildings allows to ensure the construction of earthquake-resistant buildings in the shortest possible time. The production of panel and modular building structures in factory conditions increases the quality of construction and the seismic resistance of the structures. To reduce the seismic loads on low-rise buildings and the cost of construction, experimental and theoretical studies of low-rise and modular buildings with seismic isolation and dampers are needed. The results of experimental and numerical studies of a two-story real-life sample of a large-panel residential building with a seismic protection system at the foundation level and without it are considered. Numerical studies of a modular one-story house with a metal frame were also carried out, in which the reduction of seismic loads is ensured by the dynamic parameters of the modules and the use of dampers installed at the level of the covering between two factory-made modules. The seismicity of the construction site during the research was taken as 8 and 9 points on the scale of seismic intensity in accordance with the standard of Ukraine DSTU B B.1.1-28.